A generic microfluidic biosensor of G protein-coupled receptor activation – impedance measurements of reversible morphological changes of reverse transfected HEK293 cells on microelectrodes. Issue 65 (16th July 2015) - Srivastava, Saurabh K.; Ramaneti, Rajesh; Roelse, Margriet; Tong, Hien Duy; Vrouwe, Elwin X.; Brinkman, Aldo G. M.; de Smet, Louis C. P. M.; van Rijn, Cees J. M.; Jongsma, Maarten A.
<x xml:space="preserve">Abstract</x> Flowcell with micro-IDEs (250–500 μm) covered with both stable and reverse transfected cells overexpressing membrane receptors to demonstrate impedance responses to serial injections of analyte.